PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS II SD NEGERI 025 TELUK BINJAI DUMAI TIMUR - Heldaenni Heldaenni (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
This research is motivated by the learning result of Social Sciences of second grade II students of primary school025 Teluk Binjai Dumai Timur which is still very low. This study aims to improve learning outcomes of SocialSciences students. From the data analysis there is an increase of both teacher activity, student activity, andstudent learning result, that is teacher activity at meeting 1 cycle I the percentage is 64% (enough) and atmeeting 2 increase to 76% (good). In the second cycle of meeting 3 increased again to 88% (very good) and at4th meeting increased to 96% (very good). Judging from the student activity also increased from the 1st cyclemeeting I was 62,5% (enough) and at the 2nd meeting increased to 70.83% (good). In cycle II the 3rd meetingincreased to 83,83% (good) and at the 4th meeting to 91.66% (very good). Judging from student learningoutcomes, the average base score of 60 increased to 70 in the first cycle of increase 10 points later in cycle IIincreased to 90 in cycle II large increase of 20 points. From the data analysis there is an increase both fromteacher activity, student activity, and student learning outcomes. It can be concluded that the advancement of themodel of cooperative learning type make a match can improve the learning result of Social Sciences of secondgrade students of SD Negeri 025 Teluk Binjai Dumai Timur.